"New" Antigenic Targets and Methodological Approaches for Refining Laboratory Diagnosis of Antiphospholipid Syndrome. (19th March 2015) - Misasi, Roberta; Capozzi, Antonella; Longo, Agostina; Recalchi, Serena; Lococo, Emanuela; Alessandri, Cristiano; Conti, Fabrizio; Valesini, Guido; Sorice, Maurizio
Abstract : Antiphospholipid antibodies (aPLs) are a heterogeneous group of antibodies directed against phospholipids or protein/phospholipid complexes. Currently, aPLs are assessed using either "solid-phase" assays that identify anticardiolipin antibodies and anti- β 2-glycoprotein I antibodies or "liquid-phase" assay that identifies lupus anticoagulant. However, in the last few years, "new" antigenic targets and methodological approaches have been employed for refining laboratory diagnosis of antiphospholipid syndrome (APS). In this review the potential diagnostic value of antibodies to domains of β 2-GPI, prothrombin/phosphatidylserine, vimentin/cardiolipin, protein S, protein C, annexin A2, annexin A5, and phospholipid antigens is discussed. Moreover, new technical approaches, including chemiluminescence, multiline dot assay, and thin layer chromatography (TLC) immunostaining, which utilize different supports for detection of aPL, have been developed. A special focus has been dedicated on "seronegative" APS, that is, those patients with a clinical profile suggestive of APS (thromboses, recurrent miscarriages, or foetal loss), who are persistently negative for the routinely used aPL. Recent findings suggest that, in sera from patients with SN-APS, antibodies may be detected using "new" antigenic targets (mainly vimentin/cardiolipin) or methodological approaches different from traditional techniques (TLC immunostaining). Thus, APS represents a mosaic, in which antibodies against different antigenic targets may be detected thanks to the continuously evolving new technologies.